The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4236/jbm.2021.97005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID 19 Pandemic on Elective Surgical Services in Jos, North Central, Nigeria

Abstract: Background. The COVID 19 pandemic affected healthcare delivery systems worldwide. There was a redistribution of health care resources in order to deal with the effects of the pandemic, with a corresponding consequence on other clinical services rendered. The extent of this effect on other non COVID 19 related services has been reported in other centres worldwide. In our own setting, health care resources are limited with suboptimal access even in normal situations. Objective. We sought to evaluate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, the study by Ode et al in Nigeria reported that there was a significant decrease in elective surgical services provided at the hospital during the first wave of the COVID-19 pandemic compared to the corresponding period in the previous year. It was also reported that immediate measures should be taken in that regard since a decline in elective surgery services would negatively affect access to healthcare services apart from the excessive accumulation of elective surgical procedures [ 14 ]. On the other hand, a literature review conducted by Phillips et al, which included 11 reports from nine different health organizations, stated that with the global guidance of major medical associations, they agreed that elective surgical procedures should be postponed in order to minimize the risk of COVID-19 spread and to increase available hospital resources to manage the flow of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study by Ode et al in Nigeria reported that there was a significant decrease in elective surgical services provided at the hospital during the first wave of the COVID-19 pandemic compared to the corresponding period in the previous year. It was also reported that immediate measures should be taken in that regard since a decline in elective surgery services would negatively affect access to healthcare services apart from the excessive accumulation of elective surgical procedures [ 14 ]. On the other hand, a literature review conducted by Phillips et al, which included 11 reports from nine different health organizations, stated that with the global guidance of major medical associations, they agreed that elective surgical procedures should be postponed in order to minimize the risk of COVID-19 spread and to increase available hospital resources to manage the flow of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although several studies have examined the effects of the COVID-19 pandemic on neurosurgical case volume, few studies have examined the effects in Nigeria. 2,10 The purpose of this study was to compare the demographic characteristics, diagnostic classes, and surgical elective/nonelective statuses of those patients undergoing neurosurgery during the COVID-19 pandemic in 2020 with those prepandemic in 2019 in one tertiary-care Nigerian hospital.…”
Section: Introductionmentioning
confidence: 99%